Genetic variation in the functional ENG allele inherited from the non-affected parent associates with presence of pulmonary arteriovenous malformation in hereditary hemorrhagic telangiectasia 1 (HHT1) and may influence expression of PTPN14 - Letteboer, Tom G. W.; Benzinou, Michael; Merrick, Christopher B.; Quigley, David A.; Zhau, Kechen; Kim, Il-Jin; To, Minh D.; Jablons, David M.; van Amstel, Johannes K. P.; Westermann, Cornelius J. J.; Giraud, Sophie; Dupuis-Girod, Sophie; et al. (Frontiers in Genetics, 2015)
HHT shows clinical variability within and between families. Organ site and prevalence of arteriovenous malformations (AVMs) depend on the HHT causative gene and on environmental and genetic modifiers. We tested whether variation in the functional ENG allele, inherited from the unaffected parent, alters risk for pulmonary AVMs in HHT1 mutation carriers who are ENG haploinsufficient. Genetic association was found between rs10987746 of the wild type ENG allele and presence of pulmonary AVMs [relative risk = 1.3 (1.0018-1.7424)]. The rs10987746-C at-risk allele associated with lower expression of ENG RNA in a panel of human lymphoblastoid cell lines (P=0.008). Moreover, in angiogenically active human lung adenocarcinoma tissue, but not in uninvolved quiescent lung, rs10987746-C was correlated with expression of PTPN14 (P=0.0003), another modifier of HHT. Quantitative TAQMAN expression analysis in a panel of normal lung tissues from 69 genetically heterogeneous inter-specific backcross mice, demonstrated strong correlation between expression levels of Eng, Acvrl1, and Ptpn14 (r2=0.75 to 0.9, P< 1  10-12), further suggesting a direct or indirect interaction between these three genes in lung in vivo. Our data indicate that genetic variation within the single functional ENG gene influences quantitative and/or qualitative differences in ENG expression that contribute to risk of pulmonary AVMs in HHT1, and provide correlative support for PTPN14 involvement in endoglin/ALK1 lung biology in vivo. PTPN14 has been shown to be a negative regulator of Yap/Taz signaling, which is implicated in mechanotransduction, providing a possible molecular link between endoglin/ALK1 signaling and mechanical stress. EMILIN2, which showed suggestive genetic association with pulmonary AVMs, is also reported to interact with Taz in angiogenesis. Elucidation of the molecular mechanisms regulating these interactions in endothelial cells may ultimately provide more rational choices for HHT therapy.